Perbandingan RAB Rumah Tipe 36 Konsep Konvensional dan Konsep GREENSHIP HOME Berperingkat Gold - Alfajari, Muhammad Hafizh; Ardafa, M. Fahrel; Nuraini, Cut; Andriana, Melly; Ginting, Windu Terkelin (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
This study discusses the comparison of the Cost Budget Plan (RAB) for the construction of a type 36 house with two different concepts, namely the conventional concept and the Gold-rated GREENSHIP Home concept. The conventional concept refers to traditional construction methods with standard materials, while the Gold-rated GREENSHIP Home concept integrates environmentally friendly principles in design and construction, including energy efficiency, use of environmentally friendly materials, and good water management. This study aims to analyze the cost differences between the two concepts and to evaluate the long-term benefits related to energy efficiency and sustainability. The results of the study indicate that although the initial cost of construction with the GREENSHIP concept is higher, energy savings and reduction of environmental impacts in the long term provide significant economic benefits. This study provides important insights for developers and prospective homeowners to consider implementing the GREENSHIP concept in housing development planning.